Exploring epitaxial growth of ZnTe thin films on Si substrates. (August 2022) - Zhu, Xiaolong; Wu, Jianqiang; Li, Wei; Liu, Cai; Zhang, Jingquan; Hu, Songbai
Abstract: Epitaxial growth of ZnTe on Si occurred via matching of eight ZnTe (111) planes with nine Si (111) planes. However, the stacking faults existed in the ZnTe/Si system due to the release of strain energy in initial growth. To further improve ZnTe epilayer quality, different architectures containing ZnTe nucleation layer, or ZnSe buffer layer were grown on Si substrates. The fewer defects can be found across the interfaces for ZnTe/ZnSe with 12/13 or 13/14 matching and ZnSe/Si with 21/22 or 21/23 matching of major planes. Only {111}-oriented domain formed in the ZnTe epilayer for the large-lattice-mismatched samples. The improved ZnTe (111) epitaxial thin films with single domain exhibit the narrowest FWHM of ∼180 arc sec with a dislocation density of 5.14 × 10 7  cm −2 . Extra half-planar arrays formed at the interfaces of ZnTe/ZnSe, ZnSe/Si were clearly visible through inverse fast Fourier transformation images. Moreover, the fully relaxed ZnTe epilayer with the most balanced residual stress was obtained in the X and Y directions. Highlights: High-quality ZnTe epilayer was grown on Si substrates in a domain matching epitaxy framework. The epitaxial growth process or the architectural configuration can effectively inhibit the multi-domain formation. Single-domain ZnTe epilayers have the narrowest FWHM, and the lowest dislocation density for high-performance devices.